Carbon Management Accounting, Green Intellectual Capital, Carbon Tax Policy Initiative And Firms Market Performance In Mining Companies Indonesia - Suswandoyo, M.Imam (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2024)
This study aims to investigate carbon management accounting (CMA) and Green intellectual capital (GIC) on Carbon Tax Policy Initiatives and Firms Market Performance (FMP) This study uses a population of mining sector companies on the Indonesia Stock Exchange from 2021-2023. The purposive sampling method with a sample size of 15 companies. Analysis tools using Eviews 13 and panel data regression. The results showed that CMA and GIC had a positive effect on CTPI, but CMA and CTPI had no positive effect on FMP. When conducting research, there are limitations in terms of measuring CMA and GIC which depend on annual and ongoing reports with a certain level of subjectivity. This study does not use moderation and mediation variables so that the driving factors and direct and indirect relationships are unknown; and the object of this research focuses on mining listed on the IDX 2021-2023 This research is expected to make a positive contribution to the development of stakeholder theory and new insights about sustainability, especially CMA and GIC, in designing CTPI which affects FMP in the context of mining companies in developing countries Indonesia amid the pressure of global warming.